Pengolahan Limbah Cair Industri Kayu Menggunakan Metode Destilasi (Studi Kasus Industri Kayu PT. X Provinsi Jambi) - Hasan, Hadrah; Riyanti, Anggrika; Guntoro, Boby Dwi (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to determine the effectiveness of B3 wastewater treatment using the steam distillation method applied by the wood industry of PT X Jambi Province. Observations were made during activities in the September-November 2024 period. The parameters observed include TSS, BOD5, COD, phenol, total ammonia, and pH. The WWTP consists of several main components: initial collection basin, distillation basin, condenser, distillate collection basin, reuse basin, and indicator basin. The water used in the process of washing and maintenance of the glue spreader machine is partly wastewater that has been processed through the WWTP (reuse) with a daily average of 1.408 m3 / day. The analysis results show that all parameters are below the maximum limit of quality standards according to Permen LH No. 5 of 2014. The distillation method is proven to be effective in reducing contaminant levels and producing water that is suitable for reuse in industrial processes.